Blood pressure screening results in adults in Thua Thien Hue province through the program “May measurement month” 2023 of the international society of hypertension - Hoang, Anh Tien; Huynh, Van Minh; Ngo, Manh Tri; Le, Cong Toan; Nguyen, Thi Thanh Tu (Tạp chí Y Dược Huế, 2024)
Background: Hypertension is the leading disease in Vietnam and the leading risk factor for non-communicable diseases worldwide. It is a manageable and treatable condition, according to the guidelines of the Ministry of Health and the clinical practice recommendations of the Vietnam Society of Cardiovascular and the Vietnam Society of Hypertension. Therefore, hypertension screening is necessary to develop policies and intervention programs. Aim: The program “May Measurement Month” 2023 aims to survey the prevalence of hypertension, the treatment situation, control of hypertension in people in Thua Thien Hue province and associated factors surrounding hypertension. Methods: This cross-sectional study on 1033 people collected data from adult volunteers (≥ 18 years old) in Thua Thien Hue province between 7/2023 and 8/2023. Sitting blood pressure was measured in triplicate according to standardized specified methods of the International Society of Hypertension. Results: Average age 47.58 ± 15.67, there were 235 people (22.7%) had hypertension, 37 (15.7%) of whom had never been treated for hypertension before screening. A total of 198 people were on treatment with one or more types of drugs; however, 71 people (35.95%) had uncontrolled blood pressure. Factors related to hypertension include age, sex, overweight/obesity, smoking, and a medical history of conditions such as diabetes, and irregular heartbeat. History of diabetes had the most significant impact on blood pressure control. Conclusion: The hypertension percentage in Thua Thien Hue population is still high, and the rate of blood pressure control is still limited. It is necessary to intervene promptly to reduce associated factors to reduce the risk of hypertension, ensure early diagnosis, enhance cooperation between patients and doctors for personalized treatment, increase treatment effectiveness and reduce the rate of complications